PENGARUH PERSISTENSI LABA DAN GROWTH OPPORTUNITIES TERHADAP RELEVANSI NILAI LABA AKUNTANSI PADA PERUSAHAAN INDUSTRI FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2020-2025 - Dori HP Putra; Iin Syofia Yandra; Tiara Lilis Surya (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to find out: 1) Is there an effect of Profit Persistence and Growth Opportunities on the Relevance of Accounting Profit Value in Food and Beverage Industry Companies listed on the Indonesia Stock Exchange (IDX) in 2020-2025 partially or simultaneously?, 2) How much influence does Profit Persistence and Growth Opportunities have on the Relevance of Accounting Profit Value in Food and Beverage Industry Companies listed on the Indonesia Stock Exchange (IDX) Year 2020-2025. The analysis tool used in this study is multiple linear regression analysis with the help of SPSS version 26. The data source is sourced from the annual financial statements. The data collection technique is carried out with literature research techniques. The methods used are quantitative and qualitative methods, both methods are used as observations involving numbers in the form of calculations and to analyze financial data in the company by using theories or concepts as references.